Determination and Validation of Folic Acid Content in Fortified Wheat Flour by Triple Quadrupole Liquid Chromatography Tandem Mass Spectrometry - Debnath, Mousumi; Khandelwal, Mithun; Jhelum, Vishal; Jain, Renu (Current Nutrition & Food Science, 2015)
Quantification of Folic acid (FA) in fortified wheat flour was carried out using a triple quadrupole liquid chromatography tandem mass spectrometry method. The method includes FA extraction with 0.03 mM dibasic potassium phosphate buffer containing trifluoroacetic acid, mercaptoethanol, and 0.1% ascorbic acid at pH 9.2. A reverse phase separation on a C18 column by isocratic elution using ammonium acetate and acetonitrile as the mobile phase separated FA during the 5 minute run. The retention time of FA was 1.82 min. Tandem MS-MS analysis was performed in selective reaction monitoring mode (SRM). Product-ion traces at m/z 120.141, 176.055, and 295.074 were used for quantitation of FA, and traces at m/z 442.236 were used as parent mass quantified using positive heated electrospray ionization (HESI).The validated method showed linearity ranging from 1.25 to 640 ng/ml of FA and a correlation coefficient of 0.996. The limit of detection (LOD) was 0.02μg/g and the limit of quantification (LOQ) was 0.05μg/g. The recovery ranged from 72%-99% for the wheat flour spiked at different LOQ levels. No matrix effect was noted. The precision as coefficient of variation ranged from 2.34%-6.07% for spiked wheat flour samples at different LOQ levels. Extraction and quantification of total folate using a microbiological assay (MA) with Lactobacillus casei as the assay organism and Enzyme Linked Immuno Sorbent Assay (ELISA) by competitive binding rapid ELISA kit was also performed. UHPLC-MS/MS is the most sensitive method for determination of even trace level FA and hence can efficiently determine the FA fortification level.
Keywords: UHPLC-MS/MS